2020
DOI: 10.7759/cureus.11773
|View full text |Cite
|
Sign up to set email alerts
|

Survival After Hip Fracture: A Comparative Analysis Between a Private and a Public Health Center in Chile

Abstract: Barahona et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Finally, access to fracture treatment can be analyzed using hip fracture as an example. A recent study shows that patients who belong to FONASA had a greater hip fracture incidence [ 28 ]. Moreover, patients treated for hip fracture in the PHN had a higher risk to underwent non-surgical treatment, longer hospital stay, greater in-hospital mortality, and higher one-year mortality as compared to patients treated in a private institution (even if they had public insurance [ 28 - 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, access to fracture treatment can be analyzed using hip fracture as an example. A recent study shows that patients who belong to FONASA had a greater hip fracture incidence [ 28 ]. Moreover, patients treated for hip fracture in the PHN had a higher risk to underwent non-surgical treatment, longer hospital stay, greater in-hospital mortality, and higher one-year mortality as compared to patients treated in a private institution (even if they had public insurance [ 28 - 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the new century, orthopedic procedures show a great increase [1]; most of these surgeries are due to hip fractures. This is a major public health problem and is associated with a decrease in quality of life and considerable mortality [2][3][4]. Chile is no exception, and a recent study has shown that patients older than 50 years have a lower probability of dying one year after hip fracture, even more so if they are treated in a private health center [2].…”
Section: Introductionmentioning
confidence: 99%
“…This is a major public health problem and is associated with a decrease in quality of life and considerable mortality [2][3][4]. Chile is no exception, and a recent study has shown that patients older than 50 years have a lower probability of dying one year after hip fracture, even more so if they are treated in a private health center [2]. Trochanteric and subtrochanteric hip fractures are more common in women than in men, and the 1-year mortality rate is as high as 26% [3].…”
Section: Introductionmentioning
confidence: 99%